Ta’ṡīr al-Kafā’at Fī al-Insyā ‘ala al-Kafā’at Fī al-Muhādaṡat al-Yaumiyyat li Ṭullāb al-Fashl al-Ṡāliṡ bi Kulliyyat al-Mu’allimīn al-Islāmiyyat bi Ma’had Dār al-Salām Gontor al-Ḥaram al-Markaziy - Muhammad Abi Abdillah; Rahmat Hidayat Lubis (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2022)
This study aims to examine the effect of Insha' competence on daily conversation competence of 3rd grade students of KMI Gontor Ponorogo. The type of research is descriptive quantitative research (Experimental Study) with a population of 442 students, and a sample of 116 students. The researcher used the well-known Statistical Analysis Method, Product Moment to analyze the data at a significance level of 5% and 114 degrees of freedom. The results of this study are: First, the average score for insya’ lesson test of the third grade students of KMI Darussalam Gontor Islamic Institution Central Campus is 6.1. Second, there is an effect between insya' lesson on the muhadatsah ability of third grade students of KMI Darussalam Gontor Islamic Institution Central Campus and the effect is strong. This can be seen from the results of the calculation of rxy = (0.452) which is greater than the value of